Reversal of voters’ positions since the privatization of spirits sales in Washington State - Meenakshi S. Subbaraman; Yu Ye; William C. Kerr (Preventive Medicine Reports, 2020)
In 2011, Washington State voters approved Initiative 1183 (I-1183), the privatization of liquor sales. The aim here was to examine how voter support for privatization has changed since I-1183 passed. Data came from five state-representative surveys, with recruitment between 2014 and 2016 (N = 4,290). Primary outcomes were voting on I-1183 (vs. not), voting for (vs. against) I-1183, and changing vote for I-1183 to against among those who voted for it (vs. not changing). Bivariate and multivariable logistic regressions were used for analyses. Results show that voting for (vs. against) I-1183 was related to 2.59 (P < 0.001) times greater odds of wanting to change one’s vote. This difference was large enough to have changed the result of the election if voters could know their later opinions. Among those who voted for I-1183, odds of retracting support were positively related to total past 12-month drink volume. Those who agreed that number of stores selling liquor should decrease were more likely to change votes from for to against, while those who considered that youth alcohol abuse has remained the same since privatization were less likely to change votes. Thus, in the years immediately following liquor privatization in Washington State, public opinion has changed enough to shift the result of the election from supporting privatization to rejecting it. Findings are especially relevant for other US states and countries considering privatization.